Perbandingan Biomassa Pertanian sebagai Energi Terbarukan Briket Arang - Rian Christian Sondakh; Hayatudin Hayatudin (Jurnal Ilmiah Giga, 2022)
Abstract. Briquettes are renewable energy sourced from agricultural waste and used as a household fuel. The availability of farm or plantation waste is a good impetus for developing environmentally friendly briquette fuels. This study aims to determine the characteristics of briquettes from various types of agricultural biomass. The research was carried out at the Laboratory of the Faculty of Agriculture, Madako Tolitoli University, from May to June 2020. This study used a completely randomized design (CRD) with one factor: the type of briquettes consisting of 4 levels of treatment: coconut shell, coconut fiber, rice husk, and corn cobs. Each treatment was repeated three times so that there were 12 research units. The results showed that various types of biomass produced the characteristics of briquettes with better quality, which can be seen from the research parameters of moisture content, burning time, combustion speed, and density. Coconut shell biomass has more noticeable results to the moisture content obtained is 1.76%, burning time is 215.26 minutes, combustion speed is 0.005 gr/second, and density is 0.57 gr/cc. Abstrak. Briket adalah sumber energi terbarukan yang bersumber dari limbah pertanian dan digunakan sebagai bahan bakar rumah tangga. Ketersedian limbah pertanian atau perkebunan menjadi dorongan yang baik dalam pengembangan bahan bakar briket ramah lingkungan. Penelitian ini bertujuan untuk mengetahui karakteristik briket dari berbagai jenis biomassa pertanian. Penelitian ini dilaksanakan di Laboratorium Fakultas Pertanian Universitas Madako Tolitoli, dilaksanakan pada bulan Mei sampai dengan Juni 2020. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) satu faktor yaitu jenis briket yang terdiri dari 4 taraf perlakuan yaitu : tempurung kelapa, sabut kelapa, sekam padi, dan tongkol jagung. Setiap perlakuan diulang sebanyak 3 kali sehingga terdapat 12 unit penelitian. Hasil penelitian menunjukkan bahwa berbagai jenis biomassa menghasilkan karakteristik briket dengan kualitas lebih baik dapat dilihat dari parameter penelitian kadar air, lama pembakaran, kecepatan pembakaran, dan densitas. Biomassa tempurung kelapa memiliki hasil lebih menonjol dari kadar air yang didapatkan adalah 1.76 %, lama pembakaran 215.26 menit, kecepatan pembakaran 0.005 gr/detik, dan densitas 0.57 gr/cc.